Benefits and costs of nitrogen fertilizer management for climate change mitigation: Focus on India and Mexico. - Basak R (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2016)
This report analyzes the costs and benefits of managing nitrogen fertilizer in ways that also reduce greenhouse gas emissions in cereal production (rice, wheat, and maize) in India and Mexico. The purpose of this work is to inform finance needed for low emissions agricultural development. For each agricultural mitigation practice identified, the corresponding potential emissions reduction and on-farm costs and benefits (e.g., operational costs, savings, or other benefits) are provided, based on available literature.